2017
DOI: 10.1002/zaac.201700140
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the High‐Pressure Palladium Dichalcogenides Pd0.94(1)S2 and Pd0.88(1)Se2 Comprising Exceptional PdIV Oxidation States

Abstract: Abstract. Metastable palladium deficient high-pressure phases with the compositions Pd 1-x S 2 and Pd 1-x Se 2 could be obtained via highpressure/high-temperature syntheses at 7.5 GPa (Pd 0.88(1) Se 2 ) and 11.5 GPa (Pd 0.94(1) S 2 ) at 1523 K. Compared to the normal-pressure modifications they showed a significant decrease in the c-lattice parameters of Δc/c = 4.4 % (Pd 0.94(1) S 2 ) and Δc/c = 10.8 % (Pd 0.88(1) Se 2 ) accompanied by under-occupied palladium sites. Singlecrystal analyses indicated the space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
5
0
2
Order By: Relevance
“…Under pressure, the PdS 2 ‐type structure reversibly transforms to the pyrite‐type structure . The pyrite‐phase competes with the marcasite‐type structure, as it is close in energy (Δ E =6.2 kJ mol −1 for PdSe 2 ).…”
Section: Structures Of Layered Nm(d/p)csmentioning
confidence: 99%
See 1 more Smart Citation
“…Under pressure, the PdS 2 ‐type structure reversibly transforms to the pyrite‐type structure . The pyrite‐phase competes with the marcasite‐type structure, as it is close in energy (Δ E =6.2 kJ mol −1 for PdSe 2 ).…”
Section: Structures Of Layered Nm(d/p)csmentioning
confidence: 99%
“…Other phases with reduced interlayer distances can occur between these phases . In the case of PdS 2 , much higher pressures (>16 GPa) are needed to obtain the pyrite phase .…”
Section: Structures Of Layered Nm(d/p)csmentioning
confidence: 99%
“…1T, 2H, and 3R [11]. Moreover, recent studies [12][13][14][15][16][17][18][19][20] have shown that some TMDs can also exhibit orthorhombic structures, specifically pyrite and marcasite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Unter Druck verformt sich der PdS 2 ‐Strukturtyp reversibel zum Pyrit‐Strukturtyp . Die Pyrit‐Phase konkurriert mit der Markasit‐Phase, da beide ähnliche Energien zueinander aufweisen (Δ E =6.2 kJ mol −1 bei PdSe 2 ).…”
Section: Strukturen Der Schichtartigen Nm(d/p)csunclassified
“…Dazwischen können andere Phasen mit kleinerem Interlagenabstand beobachtet werden . Im Falle von PdS 2 werden viel höhere Drücke über 16 GPa benötigt, um die Pyrit‐Phase zu erhalten .…”
Section: Strukturen Der Schichtartigen Nm(d/p)csunclassified